Application of rapid prototyping technology in pump engineering - Isametova, M.; Abilezova, G.; Duisengali, A.; Tursynbayeva, A. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article presents the results of the use of rapid prototyping technology when modifying the impeller of a centrifugal pump in order to increase efficiency. As a result of the implementation of the technology, the influence of parameters such as the printing speed of the main layers, the printing speed of the current layers, the thickness of the layers on the geometric accuracy of printed products was studied. According to the results of experiments, it was revealed the effect of the feed rate on the OZ axis, an increase in speed will lead to lower surface quality, higher roughness. The distance between the layers is 0,15 mm/s, getting a roughness of Ra 6,3 microns, and in the right case we used a distance of 0,05 mm/s between the layers, getting a roughness of Ra1,6 microns. The article presents the results of the analysis of the effect of exposure time and exposure time in the UV chamber on the hardness of printed products. The article presents a method for determining and compensating the geometry of prototypes based on reverse engineering technology based on the use of an optical scanner. The tests of a centrifugal pump with a prototype of a modified wheel confirm the need for such innovations as rapid prototyping to shorten the design cycle of new products, as well as reduce the cost of their development.